FEATURES OF THE LIVER’S FUNCTIONAL STATE UNDER CONDITIONS OF CRANIO-SKELETAL INJURY COMBINED WITH BLUNT ABDOMINAL TRAUMA - Uhlyar, T.Yu.; Badiuk, M.I.; Hudyma, A.A.; Salii, M.I.; Tsymbaliuk, H.Yu.; Prokhorenko, O.O.; Maika, I.A. (World of Medicine and Biology, 2023)
Blunt abdominal trauma and cranioskeletal trauma were simulated in mature male Wistar rats. In a separate group of rats, these injuries were combined. The control group consisted of intact animals. After 1, 3, 7, 14, 21 and 28 days, the rate of bile secretion was determined in the experimental animals. It was established that in the dynamics of the post-traumatic period, the additional infliction of blunt trauma to the abdomen significantly deepens the systemic impact of cranioskeletal trauma, which is manifested by the deepening of liver dysfunction, in particular, a significant decrease in the rate of bile secretion with a minimum of 14 days after inflicting the injury. By the 28th day of the experiment, the index increases, but does not reach the control level. Therefore, the complication of cranioskeletal trauma by abdominal trauma is accompanied by an increase in the systemic impact on the body with deepening liver dysfunction, which should be taken into account when developing measures to prevent and correct multiorgan dysfunction of traumatic origin.
Keywords: abdominal and craniocerebral trauma; hip fracture; hepatic excretion